2017
DOI: 10.11118/actaun201765062123
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Electronic Data Interchange

Abstract: Implementation of electronic data interchange (EDI) is thus more desirable and will be one of the major determinants of business success of a company. Despite the current pressure of the public sphere and all the benefits that the adoption of EDI provides, the expansion of this technology is still a minority in the Czech Republic. The aim of this paper is to identify the specifics of EDI adoption, quantify their significance, mutual conditionality and propose a new general model of EDI adoption in businesses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In (Veselá, 2017), the authors focused on exploring the use of MapReduce technology in the context of financial transactions. They The research in (Vrbová et al, 2018) introduced a novel approach to enhance scalability in permission less blockchain networks through the use of proof-of-work (PoW) consensus mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In (Veselá, 2017), the authors focused on exploring the use of MapReduce technology in the context of financial transactions. They The research in (Vrbová et al, 2018) introduced a novel approach to enhance scalability in permission less blockchain networks through the use of proof-of-work (PoW) consensus mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the enterprises lack basic knowledge and sufficient awareness of the emerging technology and do not realize that EDI is a basic tool for enterprises to participate in international trade in the future. As measures to accelerate the development of EDI, the authors propose to formulate unified domestic standards, to develop security laws and regulations by an effective integration of existing laws with specific laws and regulations of logistics, trade and shipping, [25] investigates the adoption of EDI in the Czech Republic. It is found that 70% of the interrogated businesses never heard of EDI and only 2% are using it, using email as the prevailing method of communication between, business partners.…”
Section: Electronic Data Interchange In Various Countriesmentioning
confidence: 99%
“…This particular category of information technology is commonly known as an inter-organizational information system, wherein electronic data interchange (EDI) serves as an illustrative instance of such a system. The implementation of Electronic Data Interchange (EDI) has been observed to have a positive impact on inter-organizational coordination activities and the level of integration among supply chain members (Veselá, 2017). According to Choon et al ( 2010), EDIs are characterized as the electronic exchange of standardized business transactions between computer systems.…”
Section: Electronic Data Interchange and Supply Chain Performancementioning
confidence: 99%